Solo . (Grand Rapids, Michigan Blink, 2017)
Seventeen-year-old Blade, who endeavors to resolve painful issues from his past to navigate the challenges of his former rockstar father's addictions, scathing tabloid rumors, and a protected secret that threatens his own identity.